Integration of Local Wisdom in Learning Islamic History at The Faculty of Islamic Religion Undaris Ungaran - Rina Priarni; Matori Matori; Alfi Rahmawati (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to determine the extent of the integration of local wisdom in learning Islamic history at the Faculty of Islamic Studies Undaris. As we have known that one of the objectives of learning Islamic history is to help train intelligence and shape attitudes, character, and personality of students, because the content of Islamic history material contains local wisdom values. This study uses a qualitative approach. Data collection was carried out through observation, in-depth interviews and documentation. Data analysis was carried out by giving meaning to the data that was successfully collected and from that meaning conclusions were drawn. The results of the study showed that the integration of local wisdom in learning Islamic history at FAI Undaris refers to the Curriculum which is then developed in the RPS and teaching materials based on local wisdom. In the RPS and teaching materials, the values ​​of local wisdom that are to be developed are stated. Islamic history lecturers also use tools in the form of applications of active learning strategies to further maximize the integration of local wisdom and the learning objectives of Islamic history itself.